Diosgenin enhances liposome-enabled nucleic acid delivery and CRISPR/Cas9-mediated gene editing by modulating endocytic pathways - Lohchania, Brijesh; Christopher, Abisha Crystal; Arjunan, Porkizhi; Mahalingam, Gokulnath; Kathirvelu, Durga; Prasannan, Aishwarya; Venkatesan, Vigneshwaran; Taneja, Pankaj; KM, Mohan Kumar; Thangavel, Saravanabhavan; Marepally, Srujan (Frontiers in Bioengineering and Biotechnology, 2023)
CRISPR/Cas9 system holds great promise in treating genetic diseases, owing to its safe and precise genome editing. However, the major challenges lie in transiently limiting the expression of genome editing factors and achieving therapeutically relevant frequencies with fidelity for translating the technology into clinics. The recent findings demonstrated that non-viral vectors would be a potential alternative delivery system to overcome these limitations. In our previous findings, we demonstrated that liposomal formulations with amide linker-based cationic lipids and cholesterol were found to be effective in delivering various nucleic acids. In the present study, we screened steroidal sapogenins as an alternative co-lipid to cholesterol in cationic liposomal formulations and found that liposomes with diosgenin (AD, Amide lipid: Diosgenin) further improved nucleic acid delivery efficacy, in particular, delivering Cas9 pDNA and mRNA for efficient genome editing in multiple loci including AAVS1 and Hbb when compared to AC. Mechanistic insights into endocytosis of lipoplexes revealed that Diosgenin facilitated the lipoplexes, cholesterol-independent, and clathrin-mediated endocytosis, which in turn leads to increased intracellular delivery. Our study identifies Diosgenin-doped liposomes as an efficient tool to deliver CRISPR cas9 in all three forms.